2011
DOI: 10.1038/nchem.1110
|View full text |Cite
|
Sign up to set email alerts
|

Peptide–nucleotide microdroplets as a step towards a membrane-free protocell model

Abstract: Although phospholipid bilayers are ubiquitous in modern cells, their impermeability, lack of dynamic properties, and synthetic complexity are difficult to reconcile with plausible pathways of proto-metabolism, growth and division. Here, we present an alternative membrane-free model, which demonstrates that low-molecular-weight mononucleotides and simple cationic peptides spontaneously accumulate in water into microdroplets that are stable to changes in temperature and salt concentration, undergo pH-induced cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
649
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 538 publications
(714 citation statements)
references
References 31 publications
16
649
0
4
Order By: Relevance
“…To demonstrate that we can mimic these phase transitions, we conducted the dynamic dissolution and re‐assembly of coacervates in liposomes (Figure 2 a). As reported previously, complex coacervation can be well tuned through charge ratios,16 pH,2c temperature,17 and light 18. Herein, we show the dynamics by using complex coacervates composed of low‐complexity RNAs and short polyamines, which show reversible coacervation in response to temperature changes (higher or lower than the lower critical solution temperature (LCST)) 17.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…To demonstrate that we can mimic these phase transitions, we conducted the dynamic dissolution and re‐assembly of coacervates in liposomes (Figure 2 a). As reported previously, complex coacervation can be well tuned through charge ratios,16 pH,2c temperature,17 and light 18. Herein, we show the dynamics by using complex coacervates composed of low‐complexity RNAs and short polyamines, which show reversible coacervation in response to temperature changes (higher or lower than the lower critical solution temperature (LCST)) 17.…”
mentioning
confidence: 56%
“…As Figure 3 b3 shows, DNA molecules partition efficiently into the artificial organelles because of electrostatic interactions and a low dielectric constant 2c, 4, 16b. DNA most likely competes with polyU for interactions with spermine in the coacervates, probably displacing some of the polyU during partitioning.…”
mentioning
confidence: 99%
“…Compartmentalization is but one characteristic, as protocells ideally also mimic the highly crowded interior of living cells, which have total macromolecule concentrations in excess of 300 g/L (7). Examples in which compartmentalization and high local concentrations are obtained concurrently, include DNA brushes (8), aqueous two-phase systems (9), and liquid coacervates (10). Phase separation or coacervation occurs in a wide range of polymer and protein solutions, often triggered by changes in temperature or salt concentration, or by the addition of coacervating agents (11).…”
mentioning
confidence: 99%
“…The resulting polymers were referred to as proteinoids, and it was shown that under certain conditions the proteinoids assembled into microscopic spheres with diameters in the micrometer range [2]. A version of microspheres was recently investigated by Koga et al [3] who created microscopic spherical compartments composed of nucleotides and a range of cationic oligopeptides or polypeptides. Unlike lipid vesicles, the microdroplets had no surface boundary structure, and their size and sedimentation properties depended on their composition.…”
Section: Introductionmentioning
confidence: 99%